Ethical values and sustainable development: Lithuanian experience in the context of globalisation - Čiegis, Remigijus; Gavėnauskas, Algirdas; Petkevičiūtė, Nijolė; Štreimikienė, Dalia (Technological and Economic Development of Economy, 2008)
The article overviews the ethical aspects of sustainable development in Lithuania under the conditions of globalisation. With reference to the accumulated theoretical and practical material, evaluating the principles of a sustainable development implementation and the systems of ethical behaviour, further development perspectives of sustainable development on the ethical plane in Lithuania are analysed. Spirituality plays a very important role because unique values and value orientations existing in every culture influence the worldview and life perception of members of the culture. The modern, dynamic lifetime determines rapid cultural changes and many‐sided influence of one culture on another and has significant impact on implementation of sustainable development principles in Lithuania.Etinės vertybės ir darnus vystymasis: Lietuvos patirtis globalizacijos konteksteSantrauka. Straipsnyje apžvelgiami etiniai darnaus vystymosi aspektai Lietuvoje globalizacijos kontekste. Remiantis surinkta teorine ir empirine medžiaga, vertinančia darnaus vystymosi principų įgyvendinimą etiniu aspektu, pateikiamos tų principų įdiegimo Lietuvoje gairės, paremtos etinėmis vertybėmis ir dvasingumu. Dvasingumas čia atlieka iš tiesų svarbų vaidmenį, nes unikalios vertybės ir vertybinės orientacijos, būdingos tam tikroms kultūroms, daro įtaką visuomenės narių pasaulio ir gyvenimo suvokimui. Modernus ir dinamiškas šiuolaikinis gyvenimas lemia sparčius kultūros pokyčius ir stiprina vienų kultūrų įtaką kitoms.Reikšminiai žodžiai: darnus vystymasis, etika, dvasingumas, vertybės.First published online: 21 Oct 2010